1996
DOI: 10.1021/ja9613421
|View full text |Cite
|
Sign up to set email alerts
|

Li+, Na+, and K+ Binding to the DNA and RNA Nucleobases. Bond Energies and Attachment Sites from the Dissociation of Metal Ion-Bound Heterodimers

Abstract: The alkali metal ion (M+ = Li+, Na+, K+) affinities of the common DNA and RNA nucleobases are determined in the gas phase by investigating the dissociation of metal ion-bound heterodimers [nucleobase + B]M+, in which B represents a reference base of known affinity (kinetic method). The dimer ion decompositions are assessed at two different internal energies, namely from metastable precursor ions and after collisional activation. This approach makes it possible to deconvolute entropy from enthalpy and, therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

24
320
8
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(353 citation statements)
references
References 45 publications
24
320
8
1
Order By: Relevance
“…44 In this method, branching ratios are measured at different effective temperatures using bases that are structurally similar. The reference bases used in this study are not structurally similar.…”
Section: Reaction Entropymentioning
confidence: 99%
“…44 In this method, branching ratios are measured at different effective temperatures using bases that are structurally similar. The reference bases used in this study are not structurally similar.…”
Section: Reaction Entropymentioning
confidence: 99%
“…The affinities of alkali-metal ions with nucleobases have been investigated by both the kinetic method and threshold collision-induced dissociation mass spectrometry [2,3]. On the basis of the research work on the formation of gas-phase ion-molecule complexes, Fujii [4] concluded that the alkali-metal ion affinity generally followed the order of Li ϩ Ͼ Na ϩ Ͼ K ϩ .Various mass spectrometric methods have been used to characterize metal ion biomolecular interaction at the molecular level, to determine the site of metal ion attachment to the biomolecular and its effect on altering the properties and reactivities of the biomolecule [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. ESI-MS was shown to be an excellent means for characterizing of oligonucleotides [18,19], and provide unambiguous identification of singly and multiplycharged ions of deprotonated, protonated, and metalated oligonucleotides.…”
mentioning
confidence: 99%
“…Alkali-metal ion affinities are a good basis for analysis and modeling of such interactions in complex systems. The affinities of alkali-metal ions with nucleobases have been investigated by both the kinetic method and threshold collision-induced dissociation mass spectrometry [2,3]. On the basis of the research work on the formation of gas-phase ion-molecule complexes, Fujii [4] concluded that the alkali-metal ion affinity generally followed the order of Li ϩ Ͼ Na ϩ Ͼ K ϩ .…”
mentioning
confidence: 99%
“…These methods typically evaluate enthalpies of ion-molecule reactions or unimolecular dissociations of ionic adducts to derive gasphase thermodynamic properties such as bond energies and ion affinities. In some cases, the nature of the ion-molecule interaction could be further elucidated by determining the difference in the entropy changes for competing decomposition pathways [16,17]. To date, the vast majority of ion-molecule interaction studies performed by mass spectrometry focus on positive ion studies of cationic adduct species, especially protonated molecules [14] and alkali metal adducts [18 -21].…”
mentioning
confidence: 99%